2022
DOI: 10.1002/jsf2.88
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Dendrobium officinale flower soft candy preparation and evaluation of its antioxidant activity

Abstract: Background: The preparation of Dendrobium officinale flower soft candy was optimized based on orthogonal tests, texture profile analysis (TPA), and sensory properties. A concentrated flower extract served as the raw material, with gelatin and agar powder serving as the gelling agent. The optimal amount of each component in the candy was studied. Nutrient content and antioxidant activity were also determined for the soft candy. Results:The amount of each component in the candy affected the hardness, chewability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
0
1
Order By: Relevance
“…Zhenlin et al 49 . reported similar hardness and resilience values of soft candies with increased antioxidant content as the current study, while the springiness and chewiness values were higher.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Zhenlin et al 49 . reported similar hardness and resilience values of soft candies with increased antioxidant content as the current study, while the springiness and chewiness values were higher.…”
Section: Resultssupporting
confidence: 82%
“…We did not observe any significant difference in the springiness values of the samples (P > 0.05). The springiness values of jelly samples examined in the current study were generally lower than what has been reported in the literature, 33,48,49 which may be attributed to a stronger structure of the gelatin gel matrix.…”
Section: Textural Profile Analysis Of Jelly Samplescontrasting
confidence: 85%
See 1 more Smart Citation